Analisis Molekuler Tilapia Lake Virus (TiLV) di Sentra Budidaya Benih Ikan Gurami (Osphronemus goramy) Jawa Timur - Jumria, Andi; Amin, Muhamad; Mufasirin, Mufasirin (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Tilapia Lake Virus (TiLV) is a New Emerging Disease that has been defined and included in the WOAH disease list (WOAH, 2022). This virus can infect both freshwater and marine fish, causing high mortality in Ttilapia up to 90%. Reverse transcyptase method - Semi Nested Polymerase Chain Reaction (RT-snPCR) for detection of TiLV in Osphronemus goramy. TiLV was discovered for the first time in Thailand and was also found in Jogjakarta in 2021. Further research is needed to see the damage and genetic variation caused by TiLV in Osphronemus goramy. This study aims to study the genetic variability and homology of TiLV isolates in Osphronemus goramy as definitive hosts in East Java. The results showed clinical symptoms of lethargic fish, decreased appetite, abnormal behavior, reduced reflexes, sluggish movements, darker body color, congestion, thinning fins and exopthalmia. The PCR results showed that the Osphronemus goramy showing clinical symptoms of TiLV infection were all positive. The sequencing results were further identified using the BLAST program, showing the highest similarity of the genetic identity of the sample at 96.8% with TiLV from Israel (Genebank Accession Number NC 029927.1).